2022
DOI: 10.1073/pnas.2206098119
|View full text |Cite
|
Sign up to set email alerts
|

Regulated processing and secretion of a peptide precursor in cilia

Abstract: Cilia are sensory and secretory organelles that both receive information from the environment and transmit signals. Cilia-derived vesicles (ectosomes), formed by outward budding of the ciliary membrane, carry enzymes and other bioactive products; this process represents an ancient mode of regulated secretion. Peptidergic intercellular communication controls a wide range of physiological and behavioral responses and occurs throughout eukaryotes. The Chlamydomonas reinhardtii genome encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 70 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, bioactive PAM protein and its amidated products have been identified in ciliary ectosomes released during sexual reproduction in C. reinhardtii, suggesting an ancient functional connection between cilia and amidated peptide release [5]. Indeed, biochemical studies of one identified amidated product (termed GATI-amide) in C. reinhardtii revealed that the amidated propeptide precursor was processed to the final amidated product on the ciliary membrane likely during trafficking into nascent ectosomes ( [28]; this pathway is discussed in detail below.…”
Section: Cilia As a Platform For Peptidergic Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, bioactive PAM protein and its amidated products have been identified in ciliary ectosomes released during sexual reproduction in C. reinhardtii, suggesting an ancient functional connection between cilia and amidated peptide release [5]. Indeed, biochemical studies of one identified amidated product (termed GATI-amide) in C. reinhardtii revealed that the amidated propeptide precursor was processed to the final amidated product on the ciliary membrane likely during trafficking into nascent ectosomes ( [28]; this pathway is discussed in detail below.…”
Section: Cilia As a Platform For Peptidergic Signalingmentioning
confidence: 99%
“…Biochemical tools enable the processing of the large (nominally 91 kDa) proGATI precursor and the synthesis of the amidated bioactive product to be followed. In mammals, cell-type-specific subtilisinlike prohormone convertases are involved in the processing of propeptide precursors; C. reinhardtii utilizes the subtilisin-like protease VLE1 as a ciliary prohormone convertase to cleave proGATI [28]. This suggests that C. reinhardtii uses cilia and ciliary ectosomes as a platform for peptide processing and secretion.…”
Section: Regulated Processing and Secretion Of Peptidergic Signals Th...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another specialized plasma membrane structure, the primary cilium, has attracted significant interest for its ability to release ectosomes [recent reviews: ( Wang and Barr, 2018 ; Luxmi and King, 2022 ; Ojeda Naharros and Nachury, 2022 ; Vinay and Belleannee, 2022 )]. Some of the functions ascribed to ciliary ectosomes include selectively discarding proteins from the cilium ( Nager et al, 2017 ), facilitating cell cycle reentry ( Phua et al, 2017 ), and releasing bioactive proteins and peptides ( Wood et al, 2013 ; Wang et al, 2014 ; Luxmi et al, 2022 ; Walsh et al, 2022 ). Although precise molecular mechanisms driving ciliary ectosome release are unknown, the process has been shown to rely on the actin cytoskeleton in cultured cells ( Nager et al, 2017 ; Phua et al, 2017 ) and ESCRT in Chlamydomonas ( Long et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%